Hydro- and geothermal power in Iceland : a study trip. LTU and Vattenfall visit Landsvirkjun May 1-5, 2007 - Jantzer, Isabel (Luleå, 2007)
Iceland is currently constructing the largest hydropower dam in Europe, Kárahnjúkar. There are not many possibilities to visit such construction sites, as the opportunity to expand hydropower is often restricted because of environmental or regional regulations limitations. However, the study trip, which was primarily designed for the visitors from Vattenfall, gave a broad insight in the countries geology, energy resources and production, as well as industrial development in general. Godkänd; 2007; 20070907 (ysko)